Gender differences in time poverty in rural Mozambique - Diksha Arora (The University of Utah, Department of Economics, 2014)
The study examines the nature and extent of time poverty experienced by men and women in subsistence households in Mozambique. Gender roles, shaped by patriarchal norms, place heavy work obligations on women. Time-use data from a primary household survey in Mozambique is used for this analysis. The main findings suggest that women's labor allocation to economic activities is comparable to that of men. Household chores and care work are women's responsibility, which they perform with minimal assistance from men. The heavy burden of responsibilities leave women time poorer, compared to 50% of women, only 8% of men face time constraints. Women's time poverty worsens when the burden of simultaneous care work is taken into account. Not only women work longer hours, due to multi-tasking, the work tends to be more taxing. The examination of determinants of time poverty show that measures of bargaining power like assets and education do not necessarily affect time poverty faced by women.
Keywords: D13; J22; I3; J16; O55; 330; intra-household allocation; time allocation; poverty; gender; Africa